Study of Optimization of LInear Velocity of Rotary Blade and Tractor Forward Speed Ratio on Soil Pudding of Wet Field Rice - Gatot Pramuhadi; Frans Jusuf Daywin; Tineke Mandang; Oteng Haridjaja (PERTETA, 1999)
The study on optimization of linear velocity of rotary blade and tractor forward speed ratio oil soil puddling of wetjeld rice was carried out in order to find the relationship between linear velocity of rotary blade and tractor forward speed ratio (u-v ratio) and the number of tractor's pass versus soil puddling index and tractor wheel slip during the soil puddling, and todetermine the optimum u-v ratio for rice wetjeldpreparation with certain soil classijication and condition and also with certain two wheel tractor and rotary tiller.The result, using two types of two wheel tractors and rotary tillers, showed that soil puddling was extremely afSected by puddling pass Pequency. The puddling index increased with the increasing of puddling pass prequency until the soil became puddled soil, were 0. 18 up to 0.64 forjeld test I and 0.17up to 0.67 for field test 11 in average.